Innovation, science, and institutional change - Hage, Jerald, 1932-; Meeus, Marius T. H., 1957-; Edquist, Charles, 1947- (Oxford University Press, 2006)
Examining research findings and new theoretical models relating to innovation at a number of analytic levels: projects, organisations, industrial sectors, and society, this research handbook is useful for academics and researchers across the social sciences, interested in various dimensions of innovation.